Maternal feeding styles and the risk of overweight in a cohort of Caribbean infants - Amika S. Wright; Marshall K. Tulloch‐Reid; Susan M. Chang; Susan P. Walker (Wiley, 2023)
Abstract Introduction Parental feeding styles in the first years of life may increase childhood overweight risk. There are few studies on this association in children under 2 years. The current study aimed to investigate the association between maternal feeding styles and Caribbean infants' risk of overweight at 18 months and determine whether maternal depression is an important confounder in the association. Methods It is a prospective study of mother-child dyads that participated in a three‐island parenting trial. Maternal and infant characteristics were collected at infant age 6-10 weeks with maternal depression assessed using the Center for Epidemiologic Studies Depression (CES‐D) scale questionnaire. Feeding styles were measured using items from the Toddler Feeding Behaviour Questionnaire at 12 months. Infant weight and length were measured at 18 months, and infants at risk of overweight were defined as weight‐for‐length z‐scores (WLZ) > 1. Factor analysis was used to identify feeding styles and associations with overweight risk assessed using multilevel logistic regression accounting for country and health clinic. Logistic regression models were adjusted for infant and maternal covariates, with a final model including depressive symptom scores. Results Of 366 infants assessed, 18.9% were affected by the risk of overweight. Five feeding styles were identified-uninvolved, indulgent, forceful, restrictive and responsive. Only restrictive feeding was associated with an increased risk of overweight (OR [95% CI], 1.61 [1.22, 2.13]). The association strengthened after adjusting for maternal depressive symptoms (OR [95% CI], 1.79 [1.30, 2.30]), representing an 11.18% increase in the risk of overweight odds. Conclusion Interventions that address restrictive feeding may be one strategy to reduce overweight risk among Caribbean maternal-infant dyads.